Candidate Substitution and Sherly Tjoanda’s Victory in the 2024 North Maluku Regional Election: A Feminist Institutional Perspective - Neni N; Nur’aini N; Ika Arinia Indriany (Media Hukum Indonesia (MHI), 2026)
This study analyzes Sherly Tjoanda's victory in the 2024 North Maluku regional election from a feminist institutional perspective. The study aims to understand how political structures, gender norms, and institutional dynamics influence women's opportunities in local political contestation. The research uses a qualitative method with a case study approach through document analysis and media coverage. The results show that Sherly Tjoanda's victory reflects opportunities for women's representation in politics, but is still influenced by existing power structures and political networks. This suggests that increasing women’s representation depends not only on electoral opportunities but also on changes in structures and norms within the political system.